2023
DOI: 10.1128/aem.00033-23
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on the Dynamics of Salmonella enterica Prevalence and Serovar Composition in Beef Cattle Feces and Lymph Nodes and Potential Contributing Sources from the Feedlot Environment

Abstract: Salmonella contamination of beef products, specifically from the incorporation of bovine lymph nodes into ground beef, remains a food safety concern. Current postharvest Salmonella mitigation techniques do not address Salmonella bacteria that are harbored in the lymph nodes, nor is it well understood how Salmonella invades the lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Our findings are consistent with a similar study conducted in Australia that reported a higher prevalence (27.9%) of S. Anatum in beef cattle ready for slaughter [44]. This serovar has also been reported to be prevalent in cattle faeces and lymph nodes [45,46]; slaughtered pigs [47]; ground beef as well as in humans [48]. The S. Abony with MDR phenotype which was isolated from cattle and abattoir wastewater has been reported by a similar study from related sources in Nigeria further supporting our claims [17].…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with a similar study conducted in Australia that reported a higher prevalence (27.9%) of S. Anatum in beef cattle ready for slaughter [44]. This serovar has also been reported to be prevalent in cattle faeces and lymph nodes [45,46]; slaughtered pigs [47]; ground beef as well as in humans [48]. The S. Abony with MDR phenotype which was isolated from cattle and abattoir wastewater has been reported by a similar study from related sources in Nigeria further supporting our claims [17].…”
Section: Plos Onesupporting
confidence: 93%
“…Anatum in beef cattle ready for slaughter [ 44 ]. This serovar has also been reported to be prevalent in cattle faeces and lymph nodes [ 45 , 46 ]; slaughtered pigs [ 47 ]; ground beef as well as in humans [ 48 ]. The S .…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing (WGS) and bacteriophage assays were used to identify the Salmonella and phage populations in the composite environment manure pack samples. The samples were selectively enriched for Salmonella and Salmonella isolates (n = 64), originating from feces and pen environment manure pack samples from the pre-trial sampling period (Days -36 and -21), were sequenced to determine Salmonella serovars and to identify antimicrobial resistance (AMR) genes using previously described methods [18]. Specifically, all available environmental Salmonella isolates (n = 19) and up to 3 fecal Salmonella isolates per pen (n = 45) were selected.…”
Section: Pen Manure Salmonella Populationsmentioning
confidence: 99%
“…Phage spot assays were conducted to identify and develop a bacteriophage cocktail treatment that would be effective against the Salmonella serovars identified in the feedlot environment and cattle. A representative group of Salmonella isolates (n = 31) from a longitudinal study conducted in 2019 were selected to be evenly distributed across all variables of interest: 8 serovars, 7 months, 5 sample types, and 24 out of 30 pens (Table S3) [18]. This provided a robust collection of isolates that were representative of the Salmonella population from the WTAMU Feedlot during 2019.…”
Section: Bacteriophage Assays To Determine Host Rangementioning
confidence: 99%
See 1 more Smart Citation